The theory–practice challenge: International early childhood education students making connections in Australia - Elizabeth Rouse; Dawn Joseph (New Zealand Journal of Teachers' Work)
Increasing numbers of international students are enrolling in Australian universities in early childhood teaching degrees. For many of these students understanding the early childhood education pedagogies and approaches is a different way of viewing teaching and learning from their own cultural perspective. Many of these students struggle to understand the teaching and learning theory that underpins early childhood education in Australia which draws on play-based pedagogies, child centred learning, and intentional teaching. This small-scale case study sought to gain insights into how international students undertaking a Master of Teaching (Early Childhood) in an Australian university were enabled to link their theoretical learning to practical applications of being an early childhood teacher. Using questionnaire data, the study found that the international students struggled to connect the theory and pedagogical thinking that underpins early childhood education. What was most significant for these students was the experiences they gained through their practical placements.